The role of comparative fiqh in muamalat / Muhammad Hakim Azizi … [et al.] - Muhamad Shaifuddin Shah, Muhammad 'Amirul Hazim; Azizi, Muhammad Hakim; Aziz, Muhammad Amirul Firdaus; Wan Daud, Wan Abdul Rahim (2023)
There are several definitions of the meaning of Muqaran jurisprudence expressed by Muslim scholars, among them are as follows. Muqaran jurisprudence is a science that collects the opinions of an ikhtilafiyah problem in fiqh, collects, examines and studies and discusses the arguments of each opinion objectively, to be able to know the strongest opinion, that is, the opinion supported by the strongest arguments, and most in accordance with the spirit, principles, and general principles of Islamic Sharia.